2011
DOI: 10.4161/cc.10.17.17341
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of proteins to DNA double-strand breaks: MDC1 directly recruits RAP80

Abstract: DNA double-strand breaks (DSBs) are the most severe type of DNA damage. Occurrence of DSBs in the cell activates the DNA damage response (DDR), which involves signaling cascades that sense and respond to the damage. Promptly after DSB induction, DDR proteins accumulate surrounding both DNA ends and form microscopically-visible foci. Recently, we demonstrated that the key DDR protein MDC1 directly binds RAP80, an additional DDR protein that recruits BRCA1 to DSBs. We provided evidences that the MDC1-RAP80 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…After DNA damage, ATM is recruited to DSBs where it phosphorylates H2AX 1 , and then γ-H2AX serves as a docking platform for MDC1, which binds to γ-H2AX via its tBRCT domain 17 . Abrogation of the MDC1-γ-H2AX interaction disrupts IR-induced MDC1 foci formation and renders cells radiosensitive 45 . In this study, we observed the interaction between MDC1 and γ-H2AX was abolished by depletion of ID3.…”
Section: Discussionmentioning
confidence: 99%
“…After DNA damage, ATM is recruited to DSBs where it phosphorylates H2AX 1 , and then γ-H2AX serves as a docking platform for MDC1, which binds to γ-H2AX via its tBRCT domain 17 . Abrogation of the MDC1-γ-H2AX interaction disrupts IR-induced MDC1 foci formation and renders cells radiosensitive 45 . In this study, we observed the interaction between MDC1 and γ-H2AX was abolished by depletion of ID3.…”
Section: Discussionmentioning
confidence: 99%
“…This modification appears to promote the direct interaction between a minor portion of MDC1 molecules and RAP80, and the functional significance of this interaction is supported by a RAP80 delE81 point mutation, identified in familial breast cancer, that blocks the interaction [398]. This damage-independent interaction is required for the damage-dependent recruitment of RAP80 into nuclear foci [399] discussed in the next section. As a member of the MRN complex, NBS1 promotes both NHEJ [85] and HRR [400].…”
Section: Binding Of Mdc1 To Gh2ax Facilitates Recruitment Of Key Playersmentioning
confidence: 88%
“…MDC1 also mediates recruitment of RAP80 to DNA damage foci. Although the E3 ligase remains unknown, ubiquitination of K1977 within the BRCT domain of MDC1 is required for recruitment of RAP80 to DNA DSBs (Strauss and Goldberg, 2011; Strauss et al, 2011). The K63-specific E2 Ubc13–Mms2 is required for RAP80 recruitment, implying that RAP80 is recruited to breaks through K63-linked ubiquitin chains (Strauss and Goldberg, 2011; Strauss et al, 2011).…”
Section: Rnf4: Linking Sumoylation and Ubiquitination In The Dna Damamentioning
confidence: 99%
“…Although the E3 ligase remains unknown, ubiquitination of K1977 within the BRCT domain of MDC1 is required for recruitment of RAP80 to DNA DSBs (Strauss and Goldberg, 2011; Strauss et al, 2011). The K63-specific E2 Ubc13–Mms2 is required for RAP80 recruitment, implying that RAP80 is recruited to breaks through K63-linked ubiquitin chains (Strauss and Goldberg, 2011; Strauss et al, 2011). Specifically, RAP80 is targeted to ubiquitin–SUMO hybrid chains through its SIM and two UIMs, and mutation of either the UIMs or the SIM in RAP80 decreases RAP80 recruitment to repair centers (Guzzo et al, 2012; Hu et al, 2012).…”
Section: Rnf4: Linking Sumoylation and Ubiquitination In The Dna Damamentioning
confidence: 99%